Marketing social e educação ambiental: análise de campanhas publicitárias e outras iniciativas públicas contra a poluição hídrica em Manaus - Procópio, João Vítor Lima (2023)
Manaus' urbanization was marked by igarapé3 -alterating processes, through channeling and embankments, which began in the nineteenth century, as well as through human occupation on its riverbanks, dumping of sewage and garbage. In this context, the following municipal measures of urban solid waste (USW) 4 management were analyzed: cleaning of shores and streams, garbage men of joy, voluntary delivery points, scheduled collection of large objects and dismantling of inappropriate trash cans. The research is explanatory, bibliographic, qualitative and quantitative with a questionnaire application by volunteering. In their textual and visual aspects, the environmental education campaigns presented restrain pollution of water resources, highlight the negative consequences of this action, and also publicize the municipal services mentioned above. In addition, social marketing’s ability to change values and mediate behaviors that lead to environmental education and conscious consumption was verified. Finally, was observed the need for overt, continuous and multimedia environmental social marketing campaigns to combat river pollution in Manaus.